2014
DOI: 10.1159/000358654
|View full text |Cite
|
Sign up to set email alerts
|

MiR-291b-3p Induces Apoptosis in Liver Cell Line NCTC1469 by Reducing the Level of RNA-binding Protein HuR

Abstract: Background: There is increasing evidence that miRNAs are involved in cellular apoptosis. However, the specific role of miR-291b-3p in apoptosis has not been elucidated. In the present study, we investigated the effect of miR-291b-3p on NCTC1469 cell growth and apoptosis. Methods: Cell viability and apoptosis were examined in NCTC1469 cells transfected with miR-291b-3p mimics, inhibitor miRNA or negative control. Using computational miRNA target prediction databases, HuR was predicted as a target of miR-291b-3p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 44 publications
2
39
0
Order By: Relevance
“…Recently, miR-122, miR-33, miR-30c, miR-24, and miR-130 have been identified as important regulators of lipid metabolism (18 -22). In a previous microarray screening, we found that miR-291b-3p was in-creased in the steatotic liver of db/db mice (23). MiR-291b-3p is in the murine miR-290 cluster, and previous studies have suggested a role for this miRNA in the development of embryonic stem cells (24 -26).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Recently, miR-122, miR-33, miR-30c, miR-24, and miR-130 have been identified as important regulators of lipid metabolism (18 -22). In a previous microarray screening, we found that miR-291b-3p was in-creased in the steatotic liver of db/db mice (23). MiR-291b-3p is in the murine miR-290 cluster, and previous studies have suggested a role for this miRNA in the development of embryonic stem cells (24 -26).…”
mentioning
confidence: 81%
“…Transfection of miRs or siRNA was performed with HiPerFect transfection reagent (Qiagen) as previously described (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was reversed-transcribed into cDNA using the TaqMan RNA Reverse Transcription kit (Applied Biosystems; Thermo Fisher Scientific, Inc.). qPCR was performed using SYBR Green Supermix (Bio-Rad Laboratories, Inc., Hercules, CA, USA) and the iCycleriQ Real-Time PCR system (Bio-Rad Laboratories, Inc.) as described previously (19). The thermocycling conditons were as followd: at 95˚C for 10 min followed by 50 cycles of 95˚C for 10 sec, 55˚C for 10 sec and 72˚C for 5 sec; 99˚C for 1 sec; 59˚C for 15 sec; 95˚C for 1 sec; then cooling to 40˚C.…”
Section: Rna Extraction and Reverse Transcription-quantitative Polymementioning
confidence: 99%
“…Transfections were performed in 6-, 24-, or 96-well plates after seeded cells were cultured for 24 h. siRNA reagents were transfected using HiPerFect transfection reagent (QIAGEN, Germany) according to the manufacturer's protocol [18]. Briefly, 5 ×10 3 cells/cm 2 were seeded in 200 μL/cm 2 culture.…”
Section: Transfection Of Sirnasmentioning
confidence: 99%